Caribbean capacity-building program in geospatial tools - Castano, Silvia Elena; Tello Dagua, Jhon Jairo; Paz, Paula; Rivera, Ovidio; Calle, Carmen; Molina, Natalia (2023)
Main results of the program in the Caribbean disseminated through the ArcGIS Storymap App